2016
DOI: 10.1038/srep36817
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia is Associated with Fluid Imbalance and Adverse Renal Outcome in Chronic Kidney Disease Patients Treated with Diuretics

Abstract: Chronic kidney disease (CKD) is frequently complicated with hyponatremia, probably because of fluid overload or diuretic usage. Hyponatremia in CKD population is associated with increased mortality, but the effect on renal outcome was unknown. We investigated whether hyponatremia is associated with fluid status and is a prognostic indicator for adverse outcomes in a CKD cohort of 4,766 patients with 1,009 diuretic users. We found that diuretic users had worse clinical outcomes compared with diuretic non-users.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Strokes have effects on cognitive and physical behaviors, and may result in dementia, paralysis, or death (Abegaz et al, 2017). Nephrosclerosis of the kidney is also due to arteriosclerosis which stiffens the nephron, ultimately affecting renal filtration and causing electrolyte imbalances (Bidani and Griffin, 2004;Lim et al, 2016). Overall, TOD proceed through hypertension-induced microvascular injuries in the cases of retinopathy and nephropathy and through hypertension-induced macrovascular injuries in the cases of stroke and myocardial infarctions (Nadar, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Strokes have effects on cognitive and physical behaviors, and may result in dementia, paralysis, or death (Abegaz et al, 2017). Nephrosclerosis of the kidney is also due to arteriosclerosis which stiffens the nephron, ultimately affecting renal filtration and causing electrolyte imbalances (Bidani and Griffin, 2004;Lim et al, 2016). Overall, TOD proceed through hypertension-induced microvascular injuries in the cases of retinopathy and nephropathy and through hypertension-induced macrovascular injuries in the cases of stroke and myocardial infarctions (Nadar, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hyponatremia was more prevalent in participants with background CKD and this agrees with authors that reported various mechanisms through which the relationship between elevated nitrogenous waste (from declining glomerular filtration) and hyponatremia are mediated. Low level sodium, but more importantly, chloride is needed to stimulate renin secretion and for the activation of the tubuloglomerular feedback mechanism [36]. The finding of low chloride with high renin levels, for instance in Barters' syndrome, underlines this interplay.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that hyponatremia is associated with the development of AKI in hospitalized patients [39]. Other reports have suggested that hyponatremia is a significant prognostic factor for renal replacement therapy in CKD patients treated with diuretics, eventually leading to AKI [40]. Furthermore, one report showed that serum sodium itself would not have a significant effect on kidney function [41].…”
Section: Discussionmentioning
confidence: 99%